Kekerasan Verbal: Tafsir Tematik Al Qur’an dalam Term Sukhriyah, Lamz, Humazah - Miftahul a'la; Kasuwi Saeban; Ahmad Manshur (Lembaga Yasin AlSys, 2026)
Although verbal violence has been widely studied from psychological and communication perspectives, studies that specifically discuss its conceptualization in the Qur’an through thematic exegesis of the terms sukhriyah, lamz, and humazah remain limited. This study aimed to analyze the semantic nuances of these three terms, identify the hierarchy of Divine sanctions against verbal violence, and formulate their relevance to contemporary communication ethics. This study used a qualitative approach with the thematic exegesis method (tafsīr maudhū‘ī) integrated with Toshihiko Izutsu’s semantic analysis. Data were obtained through a literature review of primary sources in the form of the Qur’an and classical and modern exegetical works, supported by relevant secondary literature. The results showed that sukhriyah, lamz, and humazah represent gradations of verbal violence, ranging from superiority-based mockery and personal reproach to harsh verbal abuse. The Qur’an prohibits such behavior through a progressive and educational hierarchy of sanctions, including moral condemnation, negative social labeling as ẓālimūn, the eschatological threat of the Hellfire of Ḥuṭamah, and the door of repentance as a path to rehabilitation. These findings contribute to the development of Qur’anic communication ethics theory by offering a gradational framework of verbal violence that goes beyond the principle of positive communication alone. Thus, the Qur’anic approach provides a preventive-rehabilitative model relevant to addressing contemporary phenomena such as cyberbullying and hate speech. The implications of this study include enriching the literature on thematic exegesis and providing practical guidance for educators, parents, and digital policymakers in building a civilized communication culture based on Qur’anic values.